Dietary protein requirements and adaptive advantages in athletes - Phillips, S. (British Journal of Nutrition, 2006)
Dietary guidelines from a variety of sources are generally congruent that an adequate dietary protein intake for persons over the age of 19 is between 0·8-0·9 g protein/kg body weight/d. According to the US/Canadian Dietary Reference Intakes, the RDA for protein of 0·8 g protein/kg/d is "...the average daily intake level that is sufficient to meet the nutrient requirement of nearly all [~98 %]… healthy individuals..." The panel also states that "...no additional dietary protein is suggested for healthy adults undertaking resistance or endurance exercise." These recommendations are in contrast to recommendations from the US and Canadian Dietetic Association: "Protein recommendations for endurance and strength trained athletes range from 1·2 to 1·7 g/kg/d." The disparity between those setting dietary protein requirements and those who might be considered to be making practical recommendations for athletes is substantial. This may reflect a situation where an adaptive advantage of protein intakes higher than recommended protein requirements exists. That population protein requirements are still based on nitrogen balance may also be a point of contention since achieving balanced nitrogen intake and excretion likely means little to an athlete who has the primary goal of exercise performance. The goal of the present review is to critically analyse evidence from both acute and chronic dietary protein-based studies in which athletic performance, or correlates thereof, have been measured. An attempt will be made to distinguish between protein requirements set by data from nitrogen balance studies, and a potential adaptive 'advantage' for athletes of dietary protein in excess of the RDA.